Program Ekstrakulikuler Manajemen Berbasis Sekolah (MBS) terhadap Karakteristik Soft Skill Siswa Sekolah Dasar - Mubtadiatul Faizah; Esa Adistiya Fajarwati Mahdum; Bela Dwi Nur Cahyani; Novanda Khoirul Umam; Najwa Meylina Zahra; Nur Rohman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The effectiveness of School-Based Management (SBM)-based extracurricular programs in developing students' soft skill characteristics still faces challenges, particularly in evaluating their impact. In response to this issue, this study aims to describe the influence of SBM-based extracurricular programs on the development of elementary students’ soft skills, including leadership, discipline, responsibility, honesty, and self-confidence. This research employed a descriptive qualitative method with a case study approach conducted at SD Negeri 7 Tahunan, Jepara. Data were collected through observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman model, involving data reduction, data display, and conclusion drawing. The findings reveal that the implementation of extracurricular programs managed participatively and supported by external coaches significantly contributes to shaping students' soft skills. Students showed improvement in discipline through regular attendance and rule compliance, responsibility through task completion in groups, honesty in activity reporting, as well as leadership and confidence through participation in scouting and sports. The implementation of SBM, which involves various stakeholders such as teachers, parents, and coaches, fosters an inclusive, reflective, and sustainable learning ecosystem that effectively supports character development through non-academic activities.